THE INFLUENCE OF ULTRASONIC IMPACT PEENING (UIP) ON THE MECHANICAL PROPERTIES AND FATIGUE LIFE OF THE AA1100 ALLOY - Adil Akram Mahmood; A Kokz, Samer; Mohsen, A. M. (Journal of Applied Engineering Science, 2023)
The effects of ultrasonic impact peening (UIP) on the mechanical properties and fatigue strength of the AA1100 alloy were compared to those of the untreated alloy. The UIP technic is widely used in a variety of applications to increase the hardness, tensile strength, surface characteristics, and fatigue life of metals. Due to the plastic deformation of the surface layer, the UIP process generated compressive residual stresses in the metal’s upper layers. Extensive investigations were carried out in order to determine the significant effect of the UIP process on the mechanical characteristics and fatigue life of the metal. According to the results of the experiment, the percentage of increase in ultimate tensile strength (UTS), yield stress, and hardness were 8 %, 7.05 %, and 9 %, respectively. A substantial improvement in fatigue life of the AA1100 alloy was seen as a result of this treatment when compared to the untreated samples. The results demonstrated that the UIP is a reliable approach for generating compressive residual stresses in the AA1100 alloys, which may have a favourable influence on the fatigue behaviour of the alloys.